The Impact of Job Satisfaction and Compensation on Grab Bike Driver Performance Following the Implementation of the Grab Bike Hemat Service in Surabaya - Cinta Lasyafayza Zivana; Kustini Kustini (Jurnal Ekonomi Manajemen Sistem Informasi, 2026)
This research seeks to examine how job satisfaction and compensation impact the performance of GrabBike drivers following the launch of the GrabBike Hemat service in Surabaya City. This study utilized a quantitative method involving a survey conducted with questionnaires given to 92 participants chosen through accidental sampling according to specific criteria and through social media channels. The analysis of the data was performed using the Partial Least Square (PLS) technique with SmartPLS software. The results show that driver performance is greatly influenced by job satisfaction and compensation, with job satisfaction exerting a stronger impact than compensation. These findings indicate that increasing job satisfaction and offering appropriate compensation can improve driver effectiveness in service delivery. The research finds that enhancing driver performance can be attained by focusing more on key factors like income and benefits. In practice, businesses are urged to assess driver compensation structures and enhance work benefits and safety to enable drivers to operate more effectively and uphold service standards for clients.